Utilization of Digital Learning Media From the Perspective of Educational Management in The Era of Merdeka Belajar Curriculum at Islamic College - L. Lesnawati (Golden Ratio of Social Science and Education, 2026)
Digital transformation is prompting educational institutions to refine their academic governance and learning strategies to be more adaptable, innovative, and responsive to the needs of digital-generation students. In this context, this study aims to analyze the Utilization of Digital Learning Media from the Perspective of Educational Management in the Era of Merdeka Belajar Curriculum at an Islamic College. This research employed a mixed-methods approach, combining survey techniques, field observations, and document analysis. The research subjects included students and lecturers from various study programs that have intensively implemented digital-based learning models. The results indicate a significant increase in the use of digital learning media during the 2024–2025 period. WhatsApp is the most dominant academic communication platform, used by 95% of students and lecturers for fast and flexible academic coordination. Google Classroom has been utilized by 70% of the academic community as a platform for submitting assignments, assessing student progress, and disseminating learning materials. However, challenges remain, such as limited internet access for students in rural areas and the need for lecturers to increase their capacity in using learning technology effectively. From an educational management perspective, coordination of digital media utilization has begun to be organized through the management of digital platforms at the study program level. However, implementation remains uneven across academic units. This research makes an important contribution to the development of a digital-based education management model in the Era of Merdeka Belajar, particularly in the context of Islamic higher education institutions that face unique challenges in balancing modernity and Islamic values.